Hemodynamics in Normal Cerebral Arteries: Qualitative Comparison of 4D Phase-Contrast Magnetic Resonance and Image-Based Computational Fluid Dynamics - Cebral, Juan R. (2009)
Detailed knowledge of the hemodynamic conditions in normal cerebral arteries is important for a better understanding of the underlying mechanisms leading to the initiation and progression of cerebrovascular diseases. Information about the baseline values of hemodynamic variables such as wall shear stresses is necessary for comparison to pathological conditions such as in cerebral aneurysms or arterial stenoses. The purpose of this study was to compare the blood flow patterns in cerebral arteries of normal subjects determined by 4D phase-contrast magnetic resonance and image-based computational fluid dynamics techniques in order to assess their consistency and to highlight their differences. The goal was not to validate (or disprove) any of the two methodologies but rather to identify regions where disagreements are to be expected and to provide guidance when interpreting the data produced by each technique.